Gambaran religious commitment, self-esteem, dan kepuasan hidup berdasarkan tipe arranged-marriage pada wanita keturunan Arab Baalwy - Syihab, Aisyah; Vinaya, Vinaya (Jurnal Psikologi Ulayat: Indonesian Journal of Indigenous Psychology, 2016)
This study aims to describe the religious commitment, self-esteem, and satisfaction with life based on the types of arranged-marriage (low arranged-marriage and high-arranged-marriage) on Arabic Baalwy women. This research was conducted with two approaches, a quantitative approach with 103 female participants (age ranging from 20 to 74 years old) and qualitative approach on 9 participants of the samples. The instruments used for this research were RCI-10 (Religious Commitment Inventory), Self-Esteem Scale, Satisfaction with Life Scale, and interview guidelines. All participants were married by way of an arranged-marriage, either one of the two types of arranged-marriage. The first type (low arranged-marriage) still allows freedom to prospective female partners to accept or decline the male who was betrothed to her, while the second type (high-arranged-marriage) do not give these freedoms. The type was assessed with Arranged-marriage questionnaire that consisted of a close-ended question about the types of arranged-marriage and one open-ended question to ensure the participants’answers. The results showed that in general the level of religious commitment, self-esteem, and satisfaction with life is quite high. The results indicated that there is no significant differences between religious commitment, self-esteem, and satisfaction with life for both types of arranged-marriage. Based on the qualitative analysis, participants had no objections with their types of arranged-marriage. It was because of their obedience to their parents and God; to maintain the purity of their offspring, so that they do not lose their self-esteem within the group; and they are satisfied with the life they lead. Suggestions for further research is to explore other psychological variables in the group of Arabic Baalwy women.